Inhibition Effects of Phenols on Corrosion of Mild Steel in Three Mineral Acids - KULKARNI, D.R.; MULEY, M.R.; RODGE, J.K.; DESHPANDE, M.N. (Asian Journal of Chemistry, 2010)
Inhibition by phenols on the corrosion of mild steel in nitric acid, sulfuric acid and hydrochloric acid media has been studied. A trend observed among the phenols in corrosion inhibition efficiency is p-cresol > m-cresol > phenol > 2-naphthol > 1-naphthol > 2-nitrophenol. Amongst naphthols, 2-naphthol was stronger inhibitor than 1-naphthol which appears to be relative to their structures. In general 2-naphthol and p-cresol are found to be stronger inhibitor over the range of concentrations of acids used. While phenol m-cresol and 1-naphthol shown greater inhibition efficiency when they are applied at higher concentrations. 2-Nitrophenol shows oxidizing nature in all the acids over the range of concentrations used.